Non-mammalian models in behavioral neuroscience: consequences for biological psychiatry - Maximino, Caio; Silva, Rhayra X.; da Silva, Suéllen de Nazaré d.; Rodrigues, Laís do Socorro d.; Barbosa, Hellen; de Carvalho, Tayana S.; Leão, Luana Ketlen R.; Lima, Monica G.; Oliveira, Karen Renata M.; Herculano, Anderson M. (Frontiers in Behavioral Neuroscience, 2015)
Current models in biological psychiatry focus on a handful of model species, and the majority of work relies on data generated in rodents. However, in the same sense that a comparative approach to neuroanatomy allows for the idenfication of patterns of brain organization, the inclusion of other species and an adoption of comparative viewpoints in behavioral neuroscience could also lead to increases in knowledge relevant to biological psychiatry. Specifically, this approach could help to identify conserved features of brain structure and behavior, as well as to understand how variation in gene expression or developmental trajectories relates to variation in brain and behavior pertinent to psychiatric disorders. To achieve this goal, the current focus on mammalian species must be expanded to include other species, including non-mammalian taxa. In this article, we review behavioral neuroscientific experiments in non-mammalian species, including traditional 'model organisms' (zebrafish, Drosophila and C. elegans) as well as in other species which can be used as 'reference'. The application of these domains in biological psychiatry and their translational relevance is considered.